1997
DOI: 10.1007/s007050050091
|View full text |Cite
|
Sign up to set email alerts
|

Mother to infant transmission of coinfection by human immunodeficiency virus and hepatitis C virus: prevalence and clinical manifestations

Abstract: The prevalence and the clinical course of hepatitis C virus (HCV) infections were studied in 23 HIV-1-infected children, who were born to 22 mothers with HIV-1/HCV coinfection. During the follow-up only two children (8.7%) showed persistent anti-HCV antibodies and circulating HCV RNA. Both children, who were aged 10 and 10.6 years respectively at the end of follow-up, had chronically-evolving liver disease and autoimmune thrombocytopenia but no signs of progressive HIV disease. Based on our experience, vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
17
2
Order By: Relevance
“…HIV-infected populations are more likely to have HCV coinfections than HIV-uninfected populations [6,7]. The rate of mother-to-child transmission (MTCT) of HCV among women without HIV infection is between 3.5% and 5.0% per pregnancy [8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-infected populations are more likely to have HCV coinfections than HIV-uninfected populations [6,7]. The rate of mother-to-child transmission (MTCT) of HCV among women without HIV infection is between 3.5% and 5.0% per pregnancy [8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
“…Many of the initial studies that established higher rates of MTCT of HCV among HIV-coinfected women were performed before the widespread availability of highly active antiretroviral (ARV) therapy (HAART), when women were more likely to remain severely immunocompromised during pregnancy [15,[22][23][24][25]. Fewer studies have examined the rates of MTCT of HCV among HIV-coinfected women with well-controlled HIV disease [7]. Acquisition of HCV infection through MTCT has become a major source of pediatric infection [26,27].…”
mentioning
confidence: 99%
“…30,31,38,40 Dual virus transmission has been reported in 4% to 10% of children born to HIV/HCV-coinfected mothers. 13,30,36,38,39 HCV RNA levels are hypothesized to be higher among women coinfected with HIV than in those infected with HCV alone, which could account, in part, for the increased risk of MTCT of HCV from HIV/HCV-coinfected women; however, not all studies have found higher levels of HCV viremia among HIV-infected mothers. 24,31,35 One European study suggested that perinatal transmission of HCV may be reduced in HIV-infected women receiving combination antiretroviral therapy (cART).…”
Section: Hepatitis C Virus (Last Updated November 6 2013; Last Reviementioning
confidence: 99%
“…TTV or GBV-C transmissions are not influenced by HCV maternal co-infection [Palomba et al, 1999;Ohto et al, 2002]. Few studies focused on vertical transmission of HIV-1-HCV dual infection, reporting that vertical transmission of HIV-1-HCV dual infection occurs less frequently than transmission of HIV-1 or HCV alone [Nigro et al, 1997;Tovo et al, 1997].…”
Section: Introductionmentioning
confidence: 99%